William D. Hudson correspondence - Hudson, William D., active 1863.
ALsS (1863 July 5 and November 8) to Hudson while serving with the 90th Ohio Infantry Regiment from his mother, Nancy Hudson, of South Bloomfield, Ohio, conveying news of the war and her concern for his provisions and safety. She refers to successes of the Union Army; seige of Vicksburg, Miss.; Battle of Gettysburg, Pa.; Battle of Chickamauga, Ga.; and activities of troops under Union Generals Thomas Leonidas Crittenden, George Gordon Meade, and John M. Palmer.
Union Army soldier.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Crittenden, Thomas Leonidas, -- 1819-1893.; Meade, George Gordon, -- 1815-1872.; Palmer, John M. -- 1817-1900.; United States. -- Army. -- Ohio Infantry Regiment, 90th (1862-1865); Chickamauga, Battle of, Ga., 1863.; Gettysburg, Battle of, Gettysburg, Pa., 1863.; Georgia -- History -- Civil War, 1861-1865.; Mississippi -- History -- Civil War, 1861-1865.; Ohio -- History -- Civil War, 1861-1865.; Pennsylvania -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Equipment and supplies; Vicksburg (Miss.) -- History -- Siege, 1863.; Soldiers